ANALISIS METODE RAPID ENTIRE BODY ASSESMENT (REBA) DENGAN KELUHAN NYERI PUNGGUNG BAWAH (LOW BACK PAIN) PADA KARYAWAN OPERATOR PRODUKSI DI PT VCI INDONESIA - Attaqwa, Yusita; Kusumo, Jati; Ramadhanti, Azhara (Jurnal Inkofar, 2024)
This research was conducted at a manufacturing company that produces mining equipment such as conveyors in Cikarang. In the Galvanizing Finishing process carried out by 1 operator, namely Yuswo, lifting the product from the bottom and lifting it onto the table for the galvanizing finishing process. This product is lifted manually with a weight of 47 kg per product. During work, operators often complain of pain around the lower back area. Based on the results of a questionnaire from Nordic Body Map, workers complained of pain in the lower back area. The aim of this research is to assess and analyze the working posture of production operators and provide suggestions for improvements related to manual lifting. Measurement and analysis in this study used the REBA (Rapid Entire Body Assessment) method. Based on the results of the final score, REBA received a value of 11, which means the risk level is very high and needs immediate improvement. From the results of this research, to reduce the risk of injury to workers, proposals and improvements were made to the place for carrying out the lifting process manually.